(untitled) (Acta Polytechnica CTU Proceedings, 2017)
Recycled concrete powder (RCP) mostly consisting of cement paste could be reused as partial cement replacement. The aim of this paper is to compare hydration and mechanical properties of RCP and two types of silica sand powder (SSP). Comparison of those materials combined with cement can highlight the binder properties of recycled concrete powder. Using of two types of SSP also show an influence of their fines on hydration process and mechanical properties. Particle size analysis and calorimetric measurement were carried out and mechanical properties such as bulk density, dynamic Young’s modulus and compression strength were examine. Calorimetric measurement proves the presence of exposed non-hydrated particles in RCP that can react again. However lower density of old cement paste in RCP overweight the mentioned potential of RCP and mechanical properties are decreasing compared with reference cement paste and cement paste SSP.